Value Generation Through Public Procurement of Innovative Earth Observation Applications: Service-Dominant Logic Perspective - Eerme Tõnis; Nummela Niina (Mary Ann Liebert, 2022)
This article investigates how the implementation of a national space strategy in partnership with supranational organizations affects the development of service ecosystems of Earth Observation (EO) applications. The subject is studied through the lens of a service-dominant logic perspective, a meta-theory that seeks to explain how economic value is cocreated in business-to-business markets. Qualitative empirical research was conducted in three emerging space countries-Slovakia, Latvia, and Estonia-to understand how value-creating resource integration processes involving space downstream companies and their potential end-users are affected by adding the European Space Agency (ESA) to the ecosystem. The study's findings showed that the catalytic procurement of prototypes of new EO applications through ESA is connected to multilevel institutional changes in relevant service ecosystems. ESA's involvement facilitates more intensive interaction between EO companies and their targeted customers in dyadic relationships. Value cocreation processes are influenced by micro-, meso-, and macrolevel institutions. The study highlights the linkages between ESA's involvement and the purposeful entrepreneurial efforts of EO companies to change prevailing institutional arrangements. This institutional work is aimed at reconfiguring institutional arrangement at the mesolevel to make it more supportive to value-creating resource integration activities between actors in a service ecosystem.